Regulasi Emosi pada Guru Honorer di SMK Al-Islam Surakarta - Monika Ayu Pramesti; Dhian Riskiana Putri; Faqih Purnomosidi (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to describe emotional regulation among honorary teachers at SMK Al-Islam Surakarta. Honorary teachers often face challenges such as heavy workloads, limited salaries, and uncertain employment status. These conditions may trigger negative emotions that, if not properly managed, can interfere with teaching performance and social relationships. Therefore, emotional regulation is an essential skill that enables teachers to carry out their professional responsibilities effectively. The research employed a qualitative method using observation, in-depth interviews, and documentation. Participants consisted of five honorary teachers aged 27–34 years and two supporting informants. Data were analyzed based on four aspects of emotional regulation proposed by Gross (2014): strategies, goals, impulse control, and acceptance. The findings indicate that honorary teachers demonstrated adequate abilities in regulating their emotions. Strategies applied included self-reflection, shifting attention to positive activities such as listening to music or engaging in worship, and giving proportional warnings to students. Although they often experienced physical and psychological fatigue, the teachers were still able to maintain professionalism in their teaching roles. Negative emotions such as anger, disappointment, or stress were generally temporary and managed through acceptance and gratitude for their circumstances. Overall, emotional regulation plays a vital role in maintaining psychological stability, enhancing teaching quality, and fostering a conducive classroom atmosphere. The study highlights the importance of institutional support to help honorary teachers cope with work-related stress and sustain their professionalism in the educational environment.